Nævus verruqueux géant chez une adolescente de 15 ans: à propos d’un cas - Traoré, Békaye (Pan Afr Med J, 2018)
Verrucous nevus is a benign tumor showing a linear pattern on Blaschko lines. It is caused by mosaic mutations of the receptor FGFR3 gene. It manifests as an aesthetic disfigurement, but individuals even experience functional complications due to itchiness. Lesions may be localized or extended (giant). In our context, the scarcity of specialized centers in dermatology is a cause of diagnostic delay inducing the patient to undertake unsuitable therapies responsible for infectious or degenerative complications. We report the case of a 15-year old girl with a history of keratotic papules showing a linear pattern along the neck, the right upper limb, the flank since childhood. Histological examination confirmed the diagnosis of verrucous nevus.